2019
DOI: 10.1002/mop.31999
|View full text |Cite
|
Sign up to set email alerts
|

Configurable triple wavelength semiconductor optical amplifier fiber laser using multiple broadband mirrors

Abstract: A configurable, triple wavelength fiber laser based on broadband mirrors (BBMs) and an arrayed waveguide grating (AWG) is demonstrated. The laser uses a semiconductor optical amplifier (SOA) as the primary gain medium due to its inhomogeneous broadening property that allows for the generation high intensity lasing wavelengths. The combination of the AWG and BBMs allows for triple lasing wavelength outputs with channel spacing from 0.8 to 4.0 nm to be obtained. The generated output is adjustable between 1540.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Thus, optical amplifiers are indispensable components in long-range transmission systems. The technologies related to SOAs include optics [2,3], semiconductor [1], material [19], communication [20], and surface treatment [21] technologies. Thus, SOAs constitute an interdisciplinary research topic.…”
Section: Development Status Of Soasmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, optical amplifiers are indispensable components in long-range transmission systems. The technologies related to SOAs include optics [2,3], semiconductor [1], material [19], communication [20], and surface treatment [21] technologies. Thus, SOAs constitute an interdisciplinary research topic.…”
Section: Development Status Of Soasmentioning
confidence: 99%
“…With the new wave of wearable devices and the development of the Internet of Things economy, small and low-power electronic components are receiving increasing attention. Thus, SOAs are a topic of interest in mainstream studies [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmad et al reported a fiber laser based on multiple broadband mirrors to enable tunable multi-wavelength generation. The lasing wavelength was tuned in the range of 1540.6-1548.6 nm [13]. Kim et al reported a wavelength switchable EDFL based on a long-period fiber grating that maintained the polarization.…”
Section: Introductionmentioning
confidence: 99%